2009
DOI: 10.1159/000260374
|View full text |Cite
|
Sign up to set email alerts
|

Potential Contributions of Heat Shock Proteins to Temperature-Dependent Sex Determination in the American Alligator

Abstract: Sex determination in the American alligator depends on the incubation temperature experienced during a thermo-sensitive period (TSP), although sex determination can be ‘reversed’ by embryonic exposure to an estrogenic compound. Thus, temperature and estrogenic signals play essential roles during temperature-dependent sex determination (TSD). The genetic basis for TSD is poorly understood, although previous studies observed that many of the genes associated with genetic sex determination (GSD) are expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 121 publications
2
55
1
Order By: Relevance
“…Whether HSP90 expression increases after heat shock is used for associating with steroid hormone receptors remains unknown. Previous studies have shown that gonadal HSP27 can reduce the E2 signal directly at trans-activation, whereas gonadal HSP70A could induce E2 signaling by stimulating vitamin D signaling that leads to the induction of augmented CYP19A1 expression (Kohno et al, 2010). In this study, we found that the expressions of HSP27 and HSP70 were up-regulated after heat shock, whereas the role of increased expressions of HSP27 and HSP70 remains to be elucidated.…”
Section: Tablementioning
confidence: 56%
See 2 more Smart Citations
“…Whether HSP90 expression increases after heat shock is used for associating with steroid hormone receptors remains unknown. Previous studies have shown that gonadal HSP27 can reduce the E2 signal directly at trans-activation, whereas gonadal HSP70A could induce E2 signaling by stimulating vitamin D signaling that leads to the induction of augmented CYP19A1 expression (Kohno et al, 2010). In this study, we found that the expressions of HSP27 and HSP70 were up-regulated after heat shock, whereas the role of increased expressions of HSP27 and HSP70 remains to be elucidated.…”
Section: Tablementioning
confidence: 56%
“…Heat shock proteins (HSPs) are a class of functionally related proteins involved in the folding and unfolding of other proteins and their expressions are induced by heat and other stresses (Kohno et al, 2010). It is reported that for several steroid receptors, binding to HSP90 was required for the receptor to be in a native hormonebinding state, and for all of the receptors, hormone binding promoted dissociation of the receptor from HSP90 and conversion of the receptor to the DNA-binding state (Pratt and Toft, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation of this molecular sex assessment indicates that there is a 98.7% (213/216) concordance between histology-based sex assignment and that based on expression patterns of sexually dimorphic genes (Kohno et al 2015). RNA isolation, purification, and RT were conducted as previously reported (Kohno et al 2010). Expression levels were determined by comparison to plasmid DNA standard curves that contained known copies of each target gene amplicon.…”
Section: Qpcr To Sex Embryos and Quantify Gonadal Gene Expressionmentioning
confidence: 87%
“…The genetic basis for TSD is poorly understood, although previous studies observed that many of the genes associated with genetic sex determination (GSD) are expressed in species with TSD. HSP27, HSP70A and HSP90 ␣ are associated with an increase of 1 sex versus the other, with HSP27 and 90 ␣ favoring the male and HSP70A favoring females [Kohno et al, 2010]. It has been shown that egg incubation temperature influences sex ratio in some reptiles as the incubation temperature interferes with the aromatase activity, resulting in a sex-determination mechanism thought to be lost in mammals.…”
Section: Heat Stress and Early Embryonic Developmentmentioning
confidence: 99%